The use and misuse of technology in education: A schematic review - K. Nandagopal (AG Volumes, 2023)
Technology is a divine blessing. It's perhaps the second greatest blessing from God after life itself. It gave birth to the arts, the sciences, and whole civilizations. That much is undeniable: technology has altered our way of life. It has changed how we think about living in many ways. Without a question, technology is essential in every facet of modern life. Technology has allowed for the automation of hitherto laborious processes. Furthermore, contemporary technology has made it easier and more efficient to carry out many difficult and vital procedures. The improvement in quality of life is largely attributable to technological advancements. The educational system has been reshaped by technological advancements. No one can deny that classroom use of technology is on the rise. In reality, the introduction of computers into classrooms has made both teaching and learning simpler. Learning and instructing are more fun now that we can utilize technology. The 21st century is often thought of as the technological age. These days, technology is crucial to how we live.